IMR 665: Management of Audio Visual Records & Archives. Individual Assignment: Article summary / Muhammad Syamil Iman Mohd. Zain - Mohd Zain, Muhammad Syamil Iman (2015)
Summary of the articles: “The Conservation and Preservation of Film and Magnetic Materials (2)” and “The Public-Private Partnership Case Study in Digitization of Audiovisual Heritage.”